Milton Model Language Patterns in English Language Teaching Advertisements on Instagram - Olga Wansyan; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This paper explores the use of Milton's Language Pattern Model in English Language Teaching (ELT) advertisements on Instagram. Drawing upon Ellerton's (2006) Milton Model framework and Searle's (1969) Speech Act Theory, with a specific focus on illocutionary acts, this research aims to identify the types of Milton Model patterns present in these advertisements and analyse how they are utilized to influence potential learners. Qualitative content analysis was applied to 30 ELT advertisements from Indonesian Instagram accounts. The results show that 15 out of 20 Milton Model language patterns have been identified, accumulating 78 instances. There were four patterns that become the most common patterns, which are Universal Quantifier (13%), Pace Current Experience (13%), Presupposition (12%), and Unspecified Verb (12%). The findings of the present study demonstrate that advertisers use of Milton Model language patterns in order to implicitly make claims, develop connections with their audience, and guide the audience to the direction of desired actions. This is accomplished by using vagueness, emotional connection, and assumed truths to enhance the persuasive impact, while also utilizing linguistic functions as assertive and directive illocutionary acts. This research expands a valuable insight by uniquely integrating the analysis of Milton Model language patterns with illocutionary functions as assertive and directive acts and specific advertising objectives, offering a novel, multi-layered framework for understanding digital persuasion in the English Language Teaching (ELT).